Internet of Things (IoT) for masonry structural health monitoring (SHM): Overview and examples of innovative systems. (5th July 2021) - Scuro, C.; Lamonaca, F.; Porzio, S.; Milani, G.; Olivito, R.S.
Highlights: IoT Internet of Things Paradigm applied to masonry cultural heritage structures. SHM structural health monitoring on existing structures. 3D-FE homogeneous and heterogeneous approach with elasto-damaging materials. Review of the existing literature on combined IoT-SHM procedures. Application on two case-studies of masonry structures and FE comparisons. Abstract: The main aim of using the IoT paradigm is related to the possibility of a connectivity extension of several common SHM devices by means of Internet. The connected devices are thus able to transmit and process data, guaranteeing new scenarios in the design of acquisition systems in different fields of science and engineering. The innovations have led the researchers to extend the application of the IoT paradigm to the SHM of masonry structures making sure that the experiments conducted in this framework are able to ensure good results with promising future improvements. The main uses, to date, have been implemented, for example, to monitor individual structural elements, reducing the risks for users due to partial or total collapses of the structure, or for the identification, detection and characterization of damage and degradation of construction materials. The aim of this work is to expose a general overview of the SHM systems used by the authors for masonry structures belonging to historical and cultural heritage, arguing their use for the protection from earthquakes with related advantages. This will be shown thanks to two preliminary SHM systems designed and implemented by the authors on two case studies using IoT, described in the paper with their related cyber and physical parts.